Analisis Nilai Moral dalam Naskah Hikayat Raja-Raja Siam - Fitzgelard, Arsyita Rahma; Wirajaya, Asep Yudha (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2023)
As an art, literary works allow their readers to use their intelligence and feelings creatively. therefore, literary works such as hikayat always have messages or values, such as moral values. this study aims to describe the moral values contained in the Hikayat of the Raja-Raja Siam. Descriptive-qualitative method used in this research. Data were collected by reading and recording. Nurgiyantoro's theory on the division of moral value forms is used to analyze the data. The results of this study show three quotations about moral values in man's relationship with his God, one quotation about man's relationship with himself, and six quotations about man's relationship with others. The moral value described in the hikayat is something natural that is influenced by the prevailing norms of society. Following up on the findings in this study, the moral values contained in this saga can be used as learning materials. Â